Ato Ordinatório CMPF nº 1, de 25 de abril de 2022 - Celia Regina Souza Delgado Alvarenga (DMPF-e, Brasília, DF, 26 abr. 2022. Caderno Extrajudicial, p. 2., 2022)
Institui formulário para acompanhamento da atividade de advocacia.